2021
DOI: 10.3389/fphar.2021.674117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP3A4, CYP3A5, MDR1 and POR Genetic Polymorphisms in Immunosuppressive Treatment in Chilean Kidney Transplanted Patients

Abstract: Cyclosporine (CsA) and tacrolimus (TAC) are immunosuppressant drugs characterized by a narrow therapeutic range and high pharmacokinetic variability. The effect of polymorphisms in genes related to the metabolism and transport of these drugs, namely CYP3A4, CYP3A5, MDR1 and POR genes, has been evaluated in diverse populations. However, the impact of these polymorphisms on drug disposition is not well established in Latin American populations. Using TaqMan® probes, we determined the allelic frequency of seven v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In our study, CYP3A5*3 did not show significant association with cyclosporine clearance which is consistent with other studies that reported that the effect of CYP3A5*3 is either insignificant or very small. [28][29][30] In addition, a limitation of our study is that ~90% of the patients in our study are of European descent.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, CYP3A5*3 did not show significant association with cyclosporine clearance which is consistent with other studies that reported that the effect of CYP3A5*3 is either insignificant or very small. [28][29][30] In addition, a limitation of our study is that ~90% of the patients in our study are of European descent.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, we found in our cohort an allele frequency between these values, similar to a report with a larger cohort of unrelated Chilean volunteers and estimated Amerindian-Caucasian admixture, facilitating the comparison of different variables between the CYP3A5 subgroups ( Roco et al, 2012 ). The genetic ancestry of our patients was not assayed, but previous studies have shown differences between CYP3A5 genotype frequencies in Central and Southern Chile, being the last one characterized by a high Mapuche Native Amerindian ancestry ( Contreras-Castillo et al, 2021 ). Our patients were transplanted at a single center in Central Chile but are derived from different cities along Chile which might be associated with an increase in genetic variability.…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus is a macrolide lactone and has been a potent immunosuppressant for the prevention and/or treatment of graft rejection in solid organ transplant patients for nearly two decades (Bowman & Brennan, 2008; Contreras‐Castillo et al., 2021; Staatz & Tett, 2004). But only when tacrolimus reaches a stable and optimized blood concentration can it exert an efficient anti‐rejection effect in transplant patients without causing severe adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant difference in the tacrolimus blood concentration per dose/kg/day at 12 h (tacrolimus C 12h /dose) between the CYP3A5 *1/*3 and *3/*3 genotypes (127 � 41.6 vs. 233 � 140, p < 0.0001) (Figure 3b and Table 3). There was also a significant difference in the tacrolimus blood level per dose/kg/day at 24 h (TAC Tacrolimus is a macrolide lactone and has been a potent immunosuppressant for the prevention and/or treatment of graft rejection in solid organ transplant patients for nearly two decades (Bowman & Brennan, 2008;Contreras-Castillo et al, 2021;Staatz & Tett, 2004).…”
Section: Association Between the Genotypes And Tac Blood Concentratio...mentioning
confidence: 99%